2013
DOI: 10.1590/s0102-86502013000100005
|View full text |Cite
|
Sign up to set email alerts
|

Spinal anesthesia for elective ceasarean section: use of different doses of hyperbaric bupivacaine associated with morphine and clonidine

Abstract: The addition of morphine and clonidine to low doses of hyperbaric bupivacaine produced adequate anesthesia for cesarean section and good postoperative analgesia, without any maternal and fetal repercussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
1
14
0
2
Order By: Relevance
“…Cesarean deliveries are routinely performed under spinal anesthesia, as are total hip arthroplasty and total knee arthroplasty. 7,15 In this study, we have found that Bupivacaine (B) is the most commonly used local anesthetic agent (59%) followed by combination of bupivacaine (B) and lignocaine (L) (26%) which is quite similar to a study done in U.S. by Concepcion MA where Lidocaine, tetracaine, and bupivacaine are the local anesthetic agents most commonly employed for spinal anesthesia. 8 We have also seen that bupivacaine (0.5%) which is the most commonly employed local anesthetic agent is given by SAB mostly at the dose range of 3-4 ml followed by 2-3 ml.…”
Section: Discussionsupporting
confidence: 82%
“…Cesarean deliveries are routinely performed under spinal anesthesia, as are total hip arthroplasty and total knee arthroplasty. 7,15 In this study, we have found that Bupivacaine (B) is the most commonly used local anesthetic agent (59%) followed by combination of bupivacaine (B) and lignocaine (L) (26%) which is quite similar to a study done in U.S. by Concepcion MA where Lidocaine, tetracaine, and bupivacaine are the local anesthetic agents most commonly employed for spinal anesthesia. 8 We have also seen that bupivacaine (0.5%) which is the most commonly employed local anesthetic agent is given by SAB mostly at the dose range of 3-4 ml followed by 2-3 ml.…”
Section: Discussionsupporting
confidence: 82%
“…However, the use of the local anesthetic alone is associated with a short duration of action and infrequent occurrence of nausea in the intraoperative period during uterine and peritoneal manipulation 1,2 . Hyperbaric bupivacaine is frequently employed in doses ranging from 4.0 to 15 mg. Doses below 10 mg used alone or 8.0 mg combined with an opioid are considered low doses of local anesthetics [2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is a decrease in local anesthetic dose, minimizing the risk of maternal arterial hypotension and damage to the fetus [2][3][4][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of neuraxial opioids has been related to side effects varying in incidence and intensity, according to the dose level [2,3,35,37]. Related to intrathecal opioids, it is essential to find alternatives to improve analgesia and to reduce side effects; 1 option is the combination of local anesthetics with opioids and clonidine because these drugs have synergistic effects [8,[16][17][18][19][20][21][22][23][24][25][26][27]31]. However, based on our data, the addition of clonidine to morphine does not result in better analgesia than the use of morphine alone, in contrast with the Paech study, which showed 240 parturients divided into 6 groups that were intrathecally administered 150 μg clonidine, 100 μg morphine, or 100 μg morphine with 30, 60, 90, or 150 μg clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine is an α 2 -adrenoceptor agonist that can be used as an adjuvant to other analgesics to improve postoperative analgesia [8,[16][17][18][19][20][21][22][23][24][25][26][27]. When administered intrathecally, clonidine results in analgesia by reducing the release of substance P, modulating N-methyl-D-aspartate receptors, increasing acetylcholine concentrations in the cerebrospinal fluid, and increasing the production of nitric oxide [16,19,20,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%